The global greening continues despite increased drought stress since 2000 - Xin Chen; Tiexi Chen; Bin He; Shuci Liu; Shengjie Zhou; Tingting Shi (Global Ecology and Conservation, 2024)
Increases or decreases in remote sensing-based vegetation greenness are usually referred to as greening or browning. The CO2 fertilization along with land management determined that greening is dominant. However, recently global browning signals due to drought stress have also been widely reported. In this study, We used the four latest leaf area index (LAI) datasets to explore this controversial topic, and found that global greening was not only present (trend between 3.1–6.4 ×10−3 m2 m−2 yr−1) but also continued (growth rate trend between 3.3–6.4 ×10−4 m2 m−2 yr−2) during 2001–2020. Greening acceleration occurred in 55.15% of the globe (positive trend and positive growth rate trend), while browning acceleration occurred in only 7.28% (negative trend and positive growth rate trend). Combined with meteorological variables, we found that CO2 change dominated the LAI trend, while climate change largely determined the LAI growth rate trend. Importantly, our study highlighted that drought trend did not necessarily trigger vegetation browning, but slowed down the rate of greening.